The Correlation between Students' Simple Past Tense Mastery and Their Recount Text Writing Skill - Febri Rumanto; Irmala Sukendra; Achmad Fahrurozy (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2021)
ABSTRACT This study is to research the correlation between students' simple past tense mastery and their writing skills in recount text at eleventh grade in SMK Setia Bhakti Tangerang Municipality in school year 2020/2021. The data was analyzed by using purposive sampling technique from 28 students. The collected data were analyzed by using Pearson Product Moment Correlation. The instruments were used students' writing test in recount text and test of students' simple past tense mastery. The research finding indicated that there was moderate correlation between students' simple past tense mastery and their writing skills in recount text. It was considered that alternative hypothesis (Ha) is rejected and the null hypothesis (Ho) which stated that there is correlation between students' simple past tense mastery and their writing skills is accepted. The result of hypothesis test between students' simple past tense mastery and writing skills in recount text of the eleventh grade at SMK Setia Bhakti Tangerang Municipality showed a direct correlation. There was moderate correlation between students' simple past tense mastery and their writing skills in recount text at SMK Setia Bhakti Tangerang Municipality with r-coef=0,451. However, students should improve the way of study, used perfectly time, practice, and had good literature to read tense mastery and English book. In writing, students are very suggested to read a book. So as the scholars conversantwith conversational English support.